Learning Outcome
- Apply an algorithm to rewrite a trinomial as a four term polynomial and factor
- Use factoring by grouping to factor a trinomial
- Factor trinomials of the form ax2+bx+cax2+bx+c
- Factoring perfect square trinomials
Key words
- Prime: having only two factors; itself and 1
- Perfect square trinomial: any trinomial that factors into two identical binomials that can be written as the square of that binomial
In the last section, we looked at factoring trinomials of the form ax2+bx+cax2+bx+c by grouping. We can use a similar method to factor trinomials of the form ax2+bx+cax2+bx+c. The only difference is that we have to include the leading coefficient aa in the process. We need to find to numbers rr and ss that are factors of the product acac and that sum to bb.
The trinomial 2x2+5x+32x2+5x+3 can be rewritten as (2x+3)(x+1)(2x+3)(x+1) using this process. We begin by rewriting the original expression as 2x2+2x+3x+32x2+2x+3x+3 and then factor each portion of the expression to obtain 2x(x+1)+3(x+1)2x(x+1)+3(x+1). We then pull out the GCF of (x+1)(x+1) to find the factored expression.
Below is a summary of the steps we will use followed by an example demonstrating how to use the steps.
Factoring Trinomials in the form ax2+bx+cax2+bx+c
To factor a trinomial in the form ax2+bx+cax2+bx+c, find two integers, r and s, whose sum is b and whose product is ac.
r⋅s=a⋅cr+s=br⋅s=a⋅cr+s=b
Rewrite the trinomial as ax2+rx+sx+cax2+rx+sx+c and then use grouping and the distributive property to factor the polynomial.
The first step in this process is to figure out what two numbers to use to re-write the xx-term as the sum of two new terms. Making a table to keep track of our work is helpful. We are looking for two numbers with a product of ac=6ac=6 and a sum of b=5b=5
Factors of ac=2⋅3=6 | Sum of Factors |
---|---|
1,6 | 7 |
−1,−6 | −7 |
2,3 | 5 |
−2,−3 | −5 |
The pair r=2 and s=3 will give the correct x-coefficient of 5, so we will rewrite it using the new factors:
2x2+5x+3=2x2+2x+3x+3
Now we can group the polynomial into two binomials.
2x2+2x+3x+3=(2x2+2x)+(3x+3)
Identify the GCF of each binomial.
2x is the GCF of (2x2+2x) and 3 is the GCF of (3x+3). We use these this to rewrite the polynomial:
(2x2+2x)+(3x+3)=2x(x+1)+3(x+1)
The GCF of our new polynomial is (x+1). We factor this out as well:
2x(x+1)+3(x+1)=(x+1)(2x+3).
Sometimes it helps visually to write the polynomial as (x+1)2x+(x+1)3 before we factor out the GCF. This is purely a matter of preference. Multiplication is commutative, so order does not matter.
Now let’s see how this strategy works for factoring 6z2+11z+4.
In this trinomial, a=6, b=11, and c=4. According to the strategy, we need to find two factors, r and s, whose sum is b=11 and whose product is a⋅c=6⋅4=24. We can make a chart to organize the possible factor combinations. (Notice that this chart only has positive numbers. Since ac is positive and b is positive, we can be certain that the two factors we’re looking for are also positive numbers.)
Factors whose product is ac=24 | Sum of the factors |
---|---|
1⋅24=24 | 1+24=25 |
2⋅12=24 | 2+12=14 |
3⋅8=24 | 3+8=11 |
4⋅6=24 | 4+6=10 |
There is only one combination where the product is 24 and the sum is 11, and that is when r=3, and s=8. Let’s use these values to factor the original trinomial.
Example
Factor 6z2+11z+4.
Solution
Rewrite the middle term, 11z, as 3z+8z (from the chart above):
6z2+3z+8z+4
Group pairs. Use grouping to consider the terms in pairs:
(6z2+3z)+(8z+4)
Factor 3z out of the first group and 4 out of the second group:
3z(2z+1)+4(2z+1)
Factor out (2z+1):
(2z+1)(3z+4)
Answer
(2z+1)(3z+4)
Try It
Factor 10y2+23y+12
Now, let’s look at an example where c is negative.
Example
Factor 5x2+7x−6 by grouping.
Solution
We have a trinomial with a=5,b=7, and c=−6. First, determine ac=−30. We need to find two numbers with a product of −30 and a sum of 7. In the table, we list factors until we find a pair with the desired sum.
Factors of −30 | Sum of Factors |
---|---|
1,−30 | −29 |
−1,30 | 29 |
2,−15 | −13 |
−2,15 | 13 |
3,−10 | −7 |
−3,10 | 7 |
So r=−3 and s=10.
5x2−3x+10x−6Rewrite the original expression as ax2+rx+sx+c=x(5x−3)+2(5x−3)Factor out the GCF of each part=(5x−3)(x+2)Factor out the GCF of the expression
Answer
5x2+7x−6=(5x−3)(x+2)
We can check our work by multiplying to confirm that (5x−3)(x+2)=5x2+7x−6.
Try It
Factor 4x2−8x−5
We can summarize our process in the following way:
factor a trinomial in the form ax2+bx+c
- List factors of ac.
- Find r and s, a pair of factors of ac with a sum of b.
- Rewrite the original expression as ax2+rx+sx+c.
- Pull out the GCF of ax2+rx.
- Pull out the GCF of sx+c.
- Factor out the GCF of the expression.
Try It
The following video presents another example of factoring a trinomial using grouping. In this example, the x-term, b, is negative. Note how having a negative middle term and a positive constant term influences the options for r and s when factoring.
Example
Factor 2x2+9x+9.
Solution
Find two numbers r and s such that r⋅s=18 and r+s=9.
9 and 18 are both positive, so we will only consider positive factors.
Factors of 2⋅9=18 | Sum of Factors |
---|---|
1,18 | 19 |
3,6 | 9 |
We can stop because we have found our factors.
Rewrite the original expression and group:
2x2+3x+6x+9=(2x2+3x)+(6x+9)
Factor out the GCF of each binomial and write as a product of two binomials:
(2x2+3x)+(6x+9)=x(2x+3)+3(2x+3)=(x+3)(2x+3)
Answer
2x2+9x+9=(x+3)(2x+3)
Try It
Factor 12x2+25x+7
Here is an example where the constant term is negative.
Example
Factor 6x2+x−1.
Solution
Determine ac=6(−1)=−6. We need two factors of ac that sum to b=1.
Factors of 6⋅−1=−6 | Sum of Factors |
---|---|
−1,6 | 5 |
1,−6 | −5 |
−2,3 | 1 |
We can stop because we have found our factors.
Rewrite the original expression and group:
6x2+x−1=6x2−2x+3x−1
Factor out the GCF of each binomial and write as a product of two binomials:
(6x2−2x)+(3x−1)=2x(3x−1)+1(3x−1)=(2x+1)(3x−1)
Answer
6x2+x−1=(2x+1)(3x−1)
Try It
Factor 6x2+53x−9
Prime Trinomials
Before going any further, it is worth mentioning that not all trinomials can be factored using integer pairs. Indeed, there are more trinomials that can’t be factored than trinomials that can be factored. Take the trinomial 2z2+35z+7, for instance. Are there two integers whose sum is b=35 and whose product is a⋅c=2⋅7=14? There are none! This type of trinomial, which cannot be factored using integers, is called a prime trinomial. We will sometimes encounter polynomials that, despite our best efforts, cannot be factored into the product of two binomials.
Example
Factor 7x2−16x–5.
Solution
Find r,s such that r⋅s=−35 and r+s=−16:
Factors of 7⋅−5=−35 | Sum of Factors |
---|---|
−1,35 | 34 |
1,−35 | −34 |
−5,7 | 2 |
−7,5 | −2 |
We have exhausted all integer pairs, so the trinomial cannot be factored. None of the factors add up to −16.
Answer
7x2−16x–5 is prime.
Try It
Factor 5x2−3x+1
Factoring out a GCF
Consider 2x2+10x+12. Since ac=2⋅12=24 and b=10, the values r=6 and s=4 can be used to rewrite the trinomial as 2x2+6x+4x+12. Factoring each pair leads to 2x(x+3)+4(x+3)=(2x+4)(x+3). But notice that this is not completely factored because the binomial 2x+4 can be further factored by pulling out the greatest common factor of 2 resulting in 2(x+2). This means that 2x2+10x+12 factors to 2(x+2)(x+3).
We really should have noticed the GCF right away: 2x2+10x+12=2(x2+5x+6). Pulling the GCF out first makes the rest of the factoring easier as we are dealing with smaller values of a,b and c. In this case,
2x2+10x+12=2(x2+5x+6)=2(x+3)(x+2)
Exactly the same answer we got before.
Consequently, we should always start factoring by looking for a GCF for all terms in the trinomial. Once we have identified and pulled out the greatest common factor, we can factor the remaining trinomial as usual.
Example
Factor 3x3–3x2–90x.
Solution
Since 3x is a common factor for the three terms, factor out the3x first:
3x(x2–x–30)
Now we can factor the trinomial x2–x–30. To find r and s, identify two numbers whose product is ac=−30 and whose sum is b=−1.
The pair of factors is −6 and 5. So replace –x with −6x+5x:
3x(x2–6x+5x–30)
Use grouping to consider the terms in pairs:
3x[(x2–6x)+(5x–30)]
Factor x out of the first group and factor 5 out of the second group:
3x[(x(x–6))+5(x–6)]
Then factor out x–6:
3x(x–6)(x+5)
Answer
3x3–3x2–90x=3x(x–6)(x+5)
Try It
Factor 30x4+27x3−27x2
Factoring out a Negative
In some situations, a is negative, as in −4h2+11h+3. It often makes sense to factor out −1 as the first step in factoring, as doing so will change the sign of ax2 from negative to positive, making the remaining trinomial easier to factor.
Example
Factor −4h2+11h+3
Solution
Factor −1 out of the trinomial. Notice that the signs of all three terms will change to their opposites:
−4h2+11h+3
=−1(4h2–11h–3)
To factor the trinomial, we need to figure out how to rewrite −11h. The product rs=4⋅−3=−12, and the sum r+s=−11.
r⋅s=−12 | r+s=−11 |
−12⋅1=−12 | −12+1=−11 |
−6⋅2=−12 | −6+2=−4 |
−4⋅3=−12 | −4+3=−1 |
Rewrite the middle term −11h as −12h+1h:
−1(4h2–12h+1h–3)
Group terms:
−1[(4h2–12h)+(1h–3)]
Factor out 4h from the first pair. The only common factor of the second group is 1, so we can write it as +1(h–3) since +1(h–3)=(h–3). This helps with factoring in the next step.
−1[4h(h–3)+1(h–3)]
Factor out a common factor of (h–3). Notice we are left with (h–3)(4h+1); the +1 comes from the term +1(h–3) in the previous step.
−1[(h–3)(4h+1)]
Answer
−4h2+11h+3=−1(h–3)(4h+1)
The following video shows an example where the leading term is negative. We will see how, by factoring out the negative sign, factoring the trinomial becomes easier.
Try It
Factor −60x5−35x4+60x3
Try It
Factor −9x3+24x2−16x
Notice that −9x3+24x2−16x factors into −x(3x−4)(3x−4), which can be written as −x(3x−4)2.
(3x−4)2 is the square of the binomial (3x−4). When (3x−4) is squared we get (3x−4)2=(3x−4)(3x−4)=9x2−24x+16. The trinomial 9x2−24x+16 is known as a perfect square trinomial.
Example
Factor 3x4−18x3+27x2
Solution
Look for a GCF first: 3x2
3x4−18x3+27x2
=3x2(x2−6x+9)
ac=9 and b=−6:
ac=9 | Sum = 6 |
9, 1 | 10 |
-9, -1 | -10 |
-9, 1 | -8 |
9, -1 | 8 |
3, 3 | 6 |
-3, -3 | -6 |
Rewrite −6x as −3x−3x:
3x2(x2−3x−3x+9)
Group and pull out the common factors:
3x2[x(x−3)−3(x−3)]
Pull out the common factor (x−3):
3x2(x−3)(x−3)
Rewrite the binomials as a perfect square:
3x2(x−3)2
Answer
3x4−18x3+27x2=3x2(x−3)2
Try It
Factor −25x2+20x−4